Śrī Svāmī Vivekānanda : jīvanī aura rāshṭrīya, sāmājika, aura dhārmika vicāroṃ kā saṅkshipta saṅgraha - Śarmā, Nanda Kumāra, 1903-1952 (SAMP early 20th-century Indian books project ;)
On the life and work of Swami Vivekananda, 1863-1902, Hindu religious leader.